Nice Ice: An Eco-postmodern Exploration of Tanya Tagaq’s Split Tooth - Ghasemi Mehdi (United Kingdom, 2025)
In this paper, I approach Tanya Tagaq’s Arctic novel Split Tooth (2018) from the perspectives of postmodern ecocriticism. I study how the novel provides readers with an opportunity to ponder on the constantly shifting and mutating ecosystems of the Arctic, while exposing human centeredness and sovereignty to decide over nature. Through a close reading of the novel, I explore a number of metanarratives, including age-old imaginations of the Arctic, and examine the ways that Tagaq employs to raise incredulity toward such established mediated assumptions of the circumpolar world. I also show how the text informs readers of indigenous peoples’ mininarratives with its revisionist accounts and challenges the monolithic conceptualization of Arctic identity. Moreover, I examine the peripheral positions of nonhuman species living in the Arctic and show how the novelist makes her text a space of alliance between human and other-than-human.
​​​​​​​